Co-Pyrolysis of Plastic Waste and Lignin: A Pathway for Enhanced Hydrocarbon Recovery - Vilmantė Kudelytė; Justas Eimontas; Rolandas Paulauskas; Nerijus Striūgas (Energies)
Various plastics and biomass wastes, such as polypropylene (PP), low- or high-density polyethylene (LDPE/HDPE), and lignin, have become some of the most concerning wastes nowadays. In this context, this study aimed to investigate the possibility of applying thermochemical processes for the valorization of these materials. The experiments were carried out using a thermogravimetric analyzer on individual plastic and lignin samples and their mixtures at different mass ratios of 1:1, 1:2, 1:3, and 1:4. The gaseous products evolved during the pyrolysis process were analyzed by combined thermogravimetric and Fourier-transform infrared spectroscopy (TG-FTIR) and chromatography-mass spectrometry (Py-GC/MS) to analyze the functional groups and chemical composition of the obtained pyrolysis products. The results showed that the main functional groups of lignin monitored by TG-FTIR were aromatic and aliphatic hydrocarbons, while all plastics showed the same results for hydrocarbons. The investigation confirmed that mixing these types of plastics with lignin at different mass ratios led to increased recovery of higher-value-added products. Py-GC/MS analysis showed that the greatest results of compound recovery were achieved with lignin and LDPE/HDPE mixtures at 600 °C. At this temperature and with a mass ratio of 1:3, the plastic’s radicals enhanced the depolymerization of lignin, encouraging its wider decomposition to hydrocarbons that can be applied for the production of value-added chemicals and bio-based energy.